BIOLOGY AND MEDICINE OF MICRO-BIOME - Pandey, Garima; Pandey, Abhay Kumar (Innovare Journal of Medical Sciences, 2017)
Humans are super organisms as they host micro-organisms to comprise 90% of cells in body and trillion foreign genes in contrast to less than 30 thousand of their own. That speaks of intricate role of microbes in human health, disease and even evolution. Medical wisdom on these aspects needs to evolve fast as modern society increasingly suffers diseases with epigenetic determinants responsible to a great extent. Appropriate address to microbiome is mandated to prevent and manage diseases due to environmental, dietary, lifestyle and medication effects. Diverse biomedical perspectives of microbiome are briefly discussed here.